STUDI KASUS KESIAPAN PENINGKATAN PERKEMBANGAN DAN KESEHATAN JIWA ANAK USAI PRASEKOLAH - Yulia Candra Ismawati; Ahmad Guntur Alfianto; Mizam Ari Kurniyanti (Institut Madani Nusantara, 2023)
The purpose of this case study is to seereadiness for increased development in preschool-aged children, in order to achieve age-appropriate growth and development, which occurs simultaneously between physical, cognitive, psychosocial, moral and spiritual. The method used is a case study by focusing on three preschool children aged 4 years. The results of this case study are that there are two aspects that have not been fulfilled in children's abilities and family abilities, which are related to children who do not want to separate from their parents, sibling rivalry and parenting styles in stimulating developmental preparations so that children can feel confident in every aspect they have such as fantasizing, high sense of initiative, curiosity, developing creativity and imagination, the ability to interact and hone children's cognitive.